Thermogravimetric and calorimetric evaluation of pellets obtained from the biomass of Coffea arabica L. - Escobar Fiesco, Germán Fabián; Ortiz, Claudia Patricia; Cardenas Torres, Rosseben Eden; Delgado, Daniel Ricardo (Ingeniería Solidaria, 2025)
Introduction: This article presents the results of the research titled Dendroenergetic Analysis of Agricultural and Forest Biomass, conducted in 2024 by Universidad América in collaboration with Fundación Universitaria Minuto de Dios (UNIMINUTO) and Politécnico Grancolombiano. Problem: Colombia is one of the world’s largest coffee producers, yet the biomass generated beyond the coffee fruit is underutilized. This biomass represents a promising source of energy. Objective: To conduct a dendroenergetic analysis of Coffea arabica L. biomass pellets by evaluating five key factors: moisture content (%), ash content (%), volatile matter, thermogravimetric properties, and calorific value. Methodology: The calorific value was evaluated using a CAL3K calorimeter, TGA 8000 thermogravimetric analyzer, the percentage of moisture was determined using a RADWAG moisture balance (±0.0001 g), and the percentage of ash and volatiles was determined using a RADWAG analytical balance (±0.0001 g). Results: The study found promising energetic properties across samples. Coal derived from the biomass showed particularly high calorific value, low volatile matter, and good resistance to moisture. These findings indicate that Coffea arabica L. biomass is a strong candidate for producing densified biofuels with high energy output. Conclusion: Given the abundant availability of Coffea arabica L. biomass in Colombia and the favorable calorific characteristics of both wood and pyrolysis charcoal, this biomass is an ideal raw material for developing sustainable, high-energy biofuels. Originality: This research provides novel dendroenergetic data on Coffea arabica L. biomass under specific conditions. Limitations: The analysis was limited to a single coffee variety.